The effect of different milk formulas on dental plaque pH - DANCHAIVIJITR, A.; NAKORNCHAI, S.; THAWEEBOON, B.; LEELATAWEEWUD, P.; PHONGHANYUDH, A.; KIATPRAJAK, C.; SURARIT, R. (International journal of paediatric dentistry, 2006)
Objectives.  The purposes of this study were (1) to investigate the effect of different milk formulas on dental plaque pH after rinsing with these three categories, type of protein‐based formulas (milk‐based, soy‐based, protein hydrolysate), type of sugar (only lactose, lactose and other sugars, only non‐milk extrinsic sugars), and casein ratio (high and low casein), and (2) to observe organic acids formed by different milk formulas. Methods.  Baseline plaque pH and plaque pH at 2, 5, 10, 15, 20, 25, 30, and 60 min after rinsing with milk formulas were recorded by a combination electrode in 14 healthy subjects. Deionized water and 10% sucrose were used as a negative and positive control. The plaque sample was also analysed to identify and quantify the organic acids using a high‐performance liquid chromatography. Parameters including minimum pH, maximum pH drop, and area under curve were compared by rmanova and paired t‐test. Results.  The minimum pH was not significantly different among different protein‐based formulas, whereas, the maximum plaque pH drop of soy‐based and milk‐based formula was significantly higher than that produced by protein hydrolysate formula (P = 0·022 and 0·03, respectively). Area under curve produced by soy‐based and milk‐based formulas was significantly larger than that created by protein hydrolysate formula (P = 0·025 and < 0·001, respectively). Milk formulas containing only lactose caused significantly less plaque pH change in minimum pH (P < 0·001), maximum pH drop (P = 0·003), and area under curve (P < 0·001) when compared with formulas containing lactose and other sugar but not with special formulas containing only non‐milk extrinsic sugar. Similarly, special formulas containing non‐milk extrinsic sugar produced significantly lower minimum pH and smaller area under curve than formulas containing lactose and other sugar did (P = 0·044 and 0·009, respectively). No different results were found between high and low casein follow‐on formulas. Lactic acid was produced more by rinsing with formulas containing lactose and other sugars than that produced by formulas containing only lactose. Conclusions.  This study suggests that milk formulas containing added other sugars tend to cause a decrease in plaque pH.